Estrogen-Related Receptor γ Induces Angiogenesis and Extracellular Matrix Degradation of Temporomandibular Joint Osteoarthritis in Rats - Zhao, Haoming; Liu, Shaopeng; Ma, Chuan; Ma, Shixing; Chen, Guokun; Yuan, Lingyu; Chen, Lei; Zhao, Huaqiang (Frontiers in Pharmacology, 2019)
The main causes of cartilage destruction during temporomandibular joint osteoarthritis (TMJOA) are extracellular matrix degradation and angiogenesis, accompanied by an increased level of matrix-degrading enzymes and proangiogenic factors. Interleukin-6 and extracellular signal-regulated kinase (ERK) signaling pathways may play a critical role in these two processes simultaneously, but researchers have not clearly determined the mechanism. We hypothesized that estrogen-related receptor γ (ERRγ) is involved in both cartilage degeneration and angiogenesis in TMJOA. The interactions between ERRγ and the Mmp9 and Vegfa promoter regions were investigated using a chromatin immunoprecipitation (ChIP) assay. A chick embryo chorioallantoic membrane (CAM) assay was performed to investigate the inhibitory effects of U0126 and GSK5182 on angiogenesis. Western blotting, RT-qPCR, immunofluorescence staining, toluidine blue staining and transfection with cDNAs or siRNAs were performed on primary mandibular condylar chondrocytes (MCCs). Unilateral anterior crossbite (UAC)-induced TMJOA models were established in rats, and Western blotting, RT-qPCR, immunohistochemistry and Safranin O-Fast Green staining were performed to evaluate changes in vivo. ERK1/2 activated matrix metalloproteinase-9 (MMP9) and vascular endothelial growth factor-A (VEGFA), which are involved in cartilage destruction, through ERRγ. Based on the ChIP assay results, ERRγ directly activated the transcription of the Mmp9 and Vegfa genes. In chick embryo CAM models, U0126 and GSK5182 significantly inhibited angiogenesis. In conclusion, ERRγ is a downstream transcription factor of ERK1/2, and its upregulation leads to extracellular matrix degradation and angiogenesis in TMJOA. This study identified a common factor between inflammation and vascularization in OA as well as a new therapeutic target for OA: ERRγ.